1997
DOI: 10.1002/(sici)1097-0177(199703)208:3<349::aid-aja6>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping expression domains of bone morphogenetic protein family members potentially account for limited tissue defects inBMP7 deficient embryos

Abstract: BMP7 is expressed at diverse sites in the developing mouse embryo, including visceral endoderm, notochord, heart, eye, kidney, and bone. A null mutation in BMP7 results in defects largely confined to the developing kidney and eye. To examine whether other bone morphogenetic protein (BMP) family members potentially substitute for BMP7 in mutant embryos, thereby restricting the observed defects, we analyzed the expression patterns of BMP2 through BMP7 in wild‐type and mutant tissues. In the central nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Unlike the chick, Bmp4 was not expressed in the dorsal neural tube but was expressed in the surface ectoderm (data not shown; Winnier et al 1995;Dudley and Robertson 1997), coelomic epithelium underlying the neural tube and somites (data not shown), and ventral mesoderm (Fig. 7G) in the tail.…”
Section: Noggin Is Required For Ventralization Of the Posterior Spinamentioning
confidence: 93%
See 1 more Smart Citation
“…Unlike the chick, Bmp4 was not expressed in the dorsal neural tube but was expressed in the surface ectoderm (data not shown; Winnier et al 1995;Dudley and Robertson 1997), coelomic epithelium underlying the neural tube and somites (data not shown), and ventral mesoderm (Fig. 7G) in the tail.…”
Section: Noggin Is Required For Ventralization Of the Posterior Spinamentioning
confidence: 93%
“…In the embryo, inhibitory BMPs could be supplied by the paraxial mesoderm itself, or by adjacent tissue. In situ hybridization studies have demonstrated that the early somite uniformly expresses Bmp3 (Dudley and Robertson 1997;J. McMahon et al, unpubl.).…”
Section: Noggin Is Required For Shh-mediated Induction Of Sclerotomalmentioning
confidence: 99%
“…In the developing retina, BMP2, BMP4, and BMP7, as well as the BMP receptors, are expressed in the chick (3) and mouse (4)(5)(6) and have been found to play a role in establishing the dorsal/ventral patterning of the retina. They also regulate the differentiation and survival of retinal neurons (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Based on in vitro and in vivo studies, it is clear that these proteins perform important roles during embryogenesis and in the adult animal. Several members of this family show overlapping patterns of expression during embryonic development, as well as functional redundancy, indicating the apparent importance of these proteins in embryogenesis (7)(8). In addition to these redundant activities, recent data generated from identification of mutations in members of this protein family clearly show specific functions for different family members.…”
mentioning
confidence: 99%
“…24). Many of these proteins are expressed in a variety of tissue and cell types during organogenesis (7,8). They seem to play an important role in mesenchymal-epithelial interactions based on their expression pattern, as well as on their in vitro and in vivo effects (3).…”
mentioning
confidence: 99%